2018
DOI: 10.1016/j.copsyc.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and human behavior: the role of individual and contextual variables

Abstract: The study of testosterone and aggression originated in experimental studies of animals, showing a direct causal link in some species. Human studies showed an overall weak correlation between testosterone and aggression. A theoretical framework ("the challenge hypothesis") enabled testosterone-behavior interactions in humans to be framed within a theory that emphasized hormonal responses to competition influencing subsequent aggressive behavior. The short-term administrations of testosterone to young women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 49 publications
7
60
0
Order By: Relevance
“…Only the difference in cortisol levels between alpha and non-alphas, however, was statistically significant. Within this context, these results are consistent with similar research in humans [13,14], and non-human primates [20] and contribute to the growing research on dual-hormone patterns with respect to testosterone and cortisol [15, 64]. For example, Sapolsky [20], found that in stable dominance hierarchies of wild olive baboons, subordinate males exhibited higher cortisol levels than alpha males.…”
Section: Discussionsupporting
confidence: 87%
“…Only the difference in cortisol levels between alpha and non-alphas, however, was statistically significant. Within this context, these results are consistent with similar research in humans [13,14], and non-human primates [20] and contribute to the growing research on dual-hormone patterns with respect to testosterone and cortisol [15, 64]. For example, Sapolsky [20], found that in stable dominance hierarchies of wild olive baboons, subordinate males exhibited higher cortisol levels than alpha males.…”
Section: Discussionsupporting
confidence: 87%
“…While mild sleep loss might reduce inhibition of reactive aggression, sleeprestricted men may not have shown more stealing than rested men because men might not inhibit this behavior even in rested conditions, as shown by their strong and reliable tendency to react to PSAP provocations with aggression (Geniole et al, 2016). The notion that sleep loss reduces men's impulses to aggress is supported by evidence that sleep deprivation lowers testosterone (e.g., Carter et al, 2012) and testosterone is associated with aggression in men, particularly those who are less able to control their impulses (Carré & Archer, 2017). The notion that sleep loss reduces men's impulses to aggress is supported by evidence that sleep deprivation lowers testosterone (e.g., Carter et al, 2012) and testosterone is associated with aggression in men, particularly those who are less able to control their impulses (Carré & Archer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…show less inhibition of aggression relative to women in part because aggression is viewed as more acceptable for men than for women (Eagly & Steffen, 1986). The notion that sleep loss reduces men's impulses to aggress is supported by evidence that sleep deprivation lowers testosterone (e.g., Carter et al, 2012) and testosterone is associated with aggression in men, particularly those who are less able to control their impulses (Carré & Archer, 2017). Cote et al (2013) reported lower reactive aggression among men who experienced a night of total sleep deprivation than among rested men.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations